2019
DOI: 10.1038/s41598-019-43887-z
|View full text |Cite
|
Sign up to set email alerts
|

QTL architecture of vine growth habit and gibberellin oxidase gene diversity in wild soybean (Glycine soja)

Abstract: Vine growth habit (VGH) is a beneficial phenotype in many wild plants, and is considered an important domesticated-related trait in soybean. However, its genetic basis remains largely unclear. Hence, in the present study we used an integrated strategy combining linkage mapping and population genome diversity analyses to reveal the genetics of VGH in soybean. In this regard, two recombinant inbred line (RIL) populations derived by crossing a common wild soybean genotype (PI342618B) with two cultivated lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…A mutation in the soybean gene GmLHY led to lower expression of GA pathway genes and reduced plant heights in young soybean plants (Cheng et al, 2019). A major quantitative trait locus (QTL) associating with the vine growth habit was found on chromosome 18 and a GA oxidase gene (VGH1) was proposed to be a candidate causal gene, although functional tests have yet to be conducted (Wang et al, 2019). A dwarf phenotype was also found in other legume crops (Hughes et al, 2020;Massawe et al, 2005;Saxena, 2008), although the genetic basis for this transition during domestication was largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation in the soybean gene GmLHY led to lower expression of GA pathway genes and reduced plant heights in young soybean plants (Cheng et al, 2019). A major quantitative trait locus (QTL) associating with the vine growth habit was found on chromosome 18 and a GA oxidase gene (VGH1) was proposed to be a candidate causal gene, although functional tests have yet to be conducted (Wang et al, 2019). A dwarf phenotype was also found in other legume crops (Hughes et al, 2020;Massawe et al, 2005;Saxena, 2008), although the genetic basis for this transition during domestication was largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A major quantitative trait locus (QTL) associating with the vine growth habit was found on chromosome 18 and a GA oxidase gene ( VGH1 ) was proposed to be a candidate causal gene, although functional tests have yet to be conducted (Wang et al. , 2019). A dwarf phenotype was also found in other legume crops (Hughes et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several traits have been selected from wild and exotic species to produce modern cultivated varieties with a suitable plant architecture and high crop productivity. Such traits include vine to erect growth habit (Wang et al, 2019 ), stem termination (Tian et al, 2010 ), and pod shattering (Dong et al, 2014 ). In this study, we identified IT208075, a simple raceme genotype having a single primary inflorescence.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutants of GA2ox responses opposite of GA20ox and GA3ox , resulting long and slender stem in pea ( Martin et al, 1999 ) and switchgrass ( Wuddineh et al, 2015 ). In soybean, Glyma18g06870 ( GAox ), 2-oxoglutarate-dependent dioxygenase is identified as a candidate gene responsible for vine growth habit (VGH) ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%